1986
DOI: 10.1007/bf01901012
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of epithelial surface membrane lipid polarity: A role for differing phospholipid translocation rates

Abstract: Large differences in lipid composition of apical and basolateral membranes from epithelial cells exist. To determine the responsible mechanism(s), rat renal cortical brush border and basolateral membrane phospholipids were labeled using 32P and either [3H]-glycerol or [2-3H] acetate for incorporation and degradation studies, respectively. Brush border and basolateral membrane fractions were isolated simultaneously from the same cortical homogenate. Different phospholipid classes were degraded at variable rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In all cases specific activities of intracellular organelle marker enzymes were less than the corresponding homogenates and there were no differences between control and experimental membrane fractions. Lipids from 0.5 to I mg of apical membrane protein were extracted in 6 ml of chloroform/ methanol (1:2), isolated by TLC, and quantitated as previously described (1,15). Protein was measured according to the method of Lowry et al (16) using BSA as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases specific activities of intracellular organelle marker enzymes were less than the corresponding homogenates and there were no differences between control and experimental membrane fractions. Lipids from 0.5 to I mg of apical membrane protein were extracted in 6 ml of chloroform/ methanol (1:2), isolated by TLC, and quantitated as previously described (1,15). Protein was measured according to the method of Lowry et al (16) using BSA as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Cholesterol transport on the other hand, which is thought to occur by a vesicular mechanism, was found to be relatively slow (halftime of 26.5 min at 25 ° C), very temperature dependent and blocked by energy poisons [9]. A study on lipid transport in epithelial cells has indicated that the very rapid transport of PC and PI is in agreement with spontaneous, possibly protein-mediated, phospholipid transport rather than a membrane flow mechanism [10]. It remains to be established whether phospholipid transfer proteins take part in this spontaneous transport of phospholipids.…”
Section: Introductionmentioning
confidence: 94%
“…Renal cortical apical (brush border membrane, BBM) and basolateral membranes (BLM) were isolated simultaneously from the same cortical homogenate and characterized enzymatically as described in detail elsewhere [30][31][32][33][34][35][36]. Briefly, the procedure entailed rapid decapsulization and removal of thin cortical slices in chilled buffer (300 mM mannitol, 5 mM ethyleneglycol-bis [/3-aminoethylether]-N, N'-tetraacetic acid, 18 mmol Tris [hydroxymethyl] aminomethane hydrochloride, 0.1 mM phenyl-methylsulfonyl fluoride) at pH 7.4.…”
Section: Preparation and Characterization Of Membrane Fractionsmentioning
confidence: 99%
“…Determinations were carried out on alkaline phosphatase, leucine aminopeptidase, and NaK-ATPase as previously reported from our laboratory [30][31][32][33][34][35][36].…”
Section: Preparation and Characterization Of Membrane Fractionsmentioning
confidence: 99%
See 1 more Smart Citation